2023
DOI: 10.1140/epjds/s13688-023-00420-7
|View full text |Cite
|
Sign up to set email alerts
|

How does Twitter account moderation work? Dynamics of account creation and suspension on Twitter during major geopolitical events

Francesco Pierri,
Luca Luceri,
Emily Chen
et al.

Abstract: Social media moderation policies are often at the center of public debate, and their implementation and enactment are sometimes surrounded by a veil of mystery. Unsurprisingly, due to limited platform transparency and data access, relatively little research has been devoted to characterizing moderation dynamics, especially in the context of controversial events and the platform activity associated with them. Here, we study the dynamics of account creation and suspension on Twitter during two global political e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…To assess this, on Jan 31, 2023, we compared the percentage of active, deleted, and suspended Twitter users in our dataset (79.5%, 13.1%, and 7.4%, respectively) with that in a sample of tweets from April 2020/March 2021 provided by the Twitter Stream Grab project ¶ (74.3%/82.2%, 18.3%/10.9%, and 7.4%/6.9%, respectively). Given that (i) suspension is often linked to bot activity (Pierri et al 2023), and that (ii) the suspension percentages are similar in our dataset on a generic sample, this suggests that overall bot activity is not unusually prominent in our sample.…”
Section: Countrymentioning
confidence: 65%
See 1 more Smart Citation
“…To assess this, on Jan 31, 2023, we compared the percentage of active, deleted, and suspended Twitter users in our dataset (79.5%, 13.1%, and 7.4%, respectively) with that in a sample of tweets from April 2020/March 2021 provided by the Twitter Stream Grab project ¶ (74.3%/82.2%, 18.3%/10.9%, and 7.4%/6.9%, respectively). Given that (i) suspension is often linked to bot activity (Pierri et al 2023), and that (ii) the suspension percentages are similar in our dataset on a generic sample, this suggests that overall bot activity is not unusually prominent in our sample.…”
Section: Countrymentioning
confidence: 65%
“…Both Sarker et al (2020) and Mackey et al (2020) studied self-reported COVID-19 symptoms and as well as recovery progression and compared them with those reported in studies conducted in clinical settings. Conceptually, the work by Paul, Dredze, and Broniatowski (2014) and Broniatowski, Paul, and Dredze (2013) is related to ours as they show that for monitoring flu activity using tweets processed by a firstperson classifier is helpful as it separates tweets discussing the flu in general from first-person reports of the flu.…”
Section: Introductionmentioning
confidence: 86%
“…Pierri et al [23] investigate the dynamics of account creation and suspension on Twitter during the Russian invasion of Ukraine and the 2022 French Presidential elections. The same authors carry out in [24] a longitudinal study of the diffusion of misinformation about the Russian invasion of Ukraine which originated from the low-credibility sources posted on Facebook and Twitter and from Russian state outlets, during the first months of the conflict.…”
Section: Related Workmentioning
confidence: 99%